Marine macroalgae: A source of chemical compounds with photoprotective and antiaging capacity¿an updated review (2021)
ABSTRACT: The biological effects of ultraviolet radiation (UVR) on the skin have been known for years, which is why there has been an increase in the use of sunscreen products, whose purpose is to protect the skin from these effects through the action of sunscreens that absorb, disperse, or reflect radiation. Sunscreens contain sun filters that act to protect human skin from the harmful biological effects of UVR. However, due to problems related to the effectiveness and safety of sunscreens in recent years, we have resorted to the search for potential photoprotective molecules from natural sources, among which are marine macroalgae which in turn are a source of molecules with potential antiaging effects. The present review shows the current state of sun filters, the mechanisms that trigger aging, and several compounds present in marine macroalgae with photoprotective and antiaging capacity with potential use in cosmetic products. The review was carried out in ScienceDirect, PubMed, and ACS, among other, databases.